2022
DOI: 10.3390/ijerph19148787
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Management, and Associated Factors of Obesity, Hypertension, and Diabetes in Tibetan Population Compared with China Overall

Abstract: Tibetans’ life expectancy lags behind China’s average. Obesity and noncommunicable diseases (NCDs) contribute to health disparity, but NCD patterns among Tibetans are unknown. To examine the prevalence, management, and associated factors for obesity, hypertension, and diabetes among Tibetans, compared with China’s average, we systematically searched PubMed and China National Knowledge Infrastructure databases for studies between January 2010 and April 2021. Thirty-nine studies were included for systematic revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…The particular high SMRs due to cardiovascular and chronic respiratory diseases in the PG may be explained by the extra stress placed on the cardiovascular and respiratory systems from the hypobaric hypoxia environment. Our recently published study showed higher hypertension prevalence among Tibetans, who usually reside on the Plateau, as compared with China's national average ( 18 , 19 , 40 ). Another earlier study also showed a positive association between altitude and hypertension.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The particular high SMRs due to cardiovascular and chronic respiratory diseases in the PG may be explained by the extra stress placed on the cardiovascular and respiratory systems from the hypobaric hypoxia environment. Our recently published study showed higher hypertension prevalence among Tibetans, who usually reside on the Plateau, as compared with China's national average ( 18 , 19 , 40 ). Another earlier study also showed a positive association between altitude and hypertension.…”
Section: Discussionmentioning
confidence: 70%
“…NCD burdens probably have contributed largely to the health disparity between the Plateau and developed areas. Our recent field study and meta-analysis showed a high prevalence of obesity, hypertension, and dyslipidemia, the metabolic risk factors of NCDs, among Tibetan adults on the Qinghai-Tibet Plateau (18)(19)(20). However, we did not find any study that investigated the NCD disparities between residents of the Qinghai-Tibet Plateau and those in developed areas.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the Tibetan children in this study demonstrate normal heart rate and blood pressure regulation. While there is a clear association between increasing altitude and the prevalence of hypertension among Tibetans (37), we argue that there are other key factors, likely unhealthy diets with excessive salt intake (32), which do not manifest in children but gradually drive the occurrence of hypertension in adults (38).…”
Section: Discussionmentioning
confidence: 81%
“…More than half of the hypertension patients under health management in PCs are not under standardized management, and low quality health management may not be effective in controlling hypertension. The quality of health management is as important as the development of management, and the management quality of PCs and NPCs needs to be further improved [ 36 , 37 ]. Strengthening the EPHS, which includes hypertension and diabetes health management services, is one of the crucial measures for the HPAP for chronic disease control.…”
Section: Discussionmentioning
confidence: 99%